Understanding how Indigenous culturally-based interventions can improve participants' health in Canada. (14th September 2017) - Murdoch-Flowers, Jayne; Tremblay, Marie-Claude; Hovey, Richard; Delormier, Treena; Gray-Donald, Katherine; Delaronde, Elaine; Macaulay, Ann C
Abstract: There is increasing recognition that culturally-based diabetes prevention programs can facilitate the adoption and maintenance of healthy behaviours in the communities in which they are implemented. The Kahnawake School Diabetes Prevention Project (KSDPP) is a health promotion, community-based participatory research project aiming to reduce the incidence of Type 2 diabetes in the community of Kahnawake (Mohawk territory, Canada), with a large range of interventions integrating a Haudenosaunee perspective of health. Building on a qualitative, naturalistic and interpretative inquiry, this study aimed to assess the outcomes of a suite of culturally-based interventions on participants' life and experience of health. Data were collected through semi-structured qualitative interviews of 1 key informant and 17 adult, female Kahnawake community members who participated in KSDPP's suite of interventions from 2007 to 2010. Grounded theory was chosen as an analytical strategy. A theoretical framework that covered the experiences of all study participants was developed from the grounded theory analysis. KSDPP's suite of interventions provided opportunities for participants to experience five different change processes: (i) Learning traditional cooking and healthy eating; (ii) Learning physical activity; (iii) Learning mind focusing and breathing techniques; (iv) Learning cultural traditions and spirituality; (v) Socializing and interacting with other participants during activities. These processes improved participants' health in four aspects: mental, physical, spiritual and social. Results of this study show how culturally-based health promotion can bring about healthy changes addressing the mental, physical, spiritual and social dimensions of a holistic concept of health, relevant to the Indigenous perspective of well-being.